A preparation method of powder material containing precious metal elements and its application
In the preparation of precious metal nanopowder materials, the distribution and phase separation of impurity elements are used to use the solidification process of the initial alloy melt to remove the matrix phase to obtain high-purity precious metal nanopowder materials, which solves the problem of difficulty in large-scale production and high purity of precious metal nanopowder materials in the prior art, and realizes a simple, low-cost and efficient preparation method.
Patent Information
- Application Number
- CN202080103275.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-16
- Filing Date
- 2020-11-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-11-23
AI Technical Summary
In the prior art, when preparing precious metal nanopowder materials, it is difficult to ensure high purity and large-scale production at the same time, and the cost is high.
By selecting the initial alloy raw material, melting according to a specific composition ratio, forming a uniform initial alloy melt, and redistributeing impurity elements through the solidification process to form a matrix phase and a diffuse particle phase, and then removing the matrix phase to obtain a high purity precious metal nanopowder material.
It realizes simple process and easy operation, and can prepare nano-, sub-micron-, and micro-level high-purity precious metal powder materials, reducing production costs and improving the purity and performance of the material.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of micro-nano materials, and in particular to a preparation method of a powder material containing precious metal elements and application thereof. Background Art
[0002] The preparation methods of ultrafine powder materials with micron, submicron and nanometer particle sizes are divided into solid phase method, liquid phase method and gas phase method according to the state of the material. Among them, the solid phase method mainly includes mechanical crushing method, ultrasonic crushing method, thermal decomposition method, explosion method, etc., the liquid phase method mainly includes precipitation method, alkoxide method, carbonyl method, spray heat drying method, freeze drying method, electrolysis method, chemical condensation method, etc., and the gas phase method mainly includes gas phase reaction method, plasma method, high temperature plasma method, evaporation method, chemical vapor deposition method, etc.
[0003] Although there are many methods for preparing ultrafine powder materials, each method has certain limitations. For example, the disadvantages of the liquid phase method are low output, high cost and complex process; the disadvantage of the mechanical method is that it is difficult to classify the powder material after it is prepared, and the purity, fineness and morphology of the product are difficult to guarantee; the rotating electrode method and the gas atomization method are currently the main methods for preparing high-performance metal and alloy powders, but the production efficiency is low, the yield is not high, and the energy consumption is relatively large; the air flow milling method and the hydrogenation dehydrogenation method are suitable for large-scale industrial production, but they are highly selective for raw materials and alloys.
[0004] Precious metal powder materials, especially precious metal nanopowder materials, are generally prepared by chemical reduction, but the chemical reduction method is generally difficult to ensure large-scale preparation of products while also ensuring good control of the particle size of the resulting precious metal nanopowder.
[0005] In addition, the impurity content of powder materials, especially the oxygen content, has a great influence on their performance. At present, the impurity content of metals or alloys is mainly controlled by controlling the purity of raw materials and the vacuum degree, which is costly. Therefore, it is of great significance to develop new preparation methods for high-purity powder materials. Summary of the invention
[0006] Based on this, it is necessary to provide a method for preparing a powder material containing precious metal elements with a simple process and easy operation to address the above problems.
[0007] A method for preparing a powder material containing precious metal elements, characterized in that it comprises the following steps:
[0008] Step S1, selecting an initial alloy raw material, melting the initial alloy raw material according to the initial alloy composition ratio, and obtaining a uniform initial alloy melt containing impurity element D; the average composition of the initial alloy melt is mainly Cu a (M x Ty ) b D d , wherein M comprises at least one of the noble metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, and Ag, T comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, and Fe, and D comprises at least one of O, H, N, P, S, F, Cl, I, and Br; and 60%≤a≤99.9%, 0.1%≤b≤40%, 0≤d≤5%; 0.1%≤x≤100%, 0%≤y≤99.9%; wherein a, b, d, and x, y represent the atomic percentage contents of the corresponding constituent elements, respectively;
[0009] Step S2, solidifying the initial alloy melt into an initial alloy strip; the solidified structure of the initial alloy strip includes a matrix phase and a dispersed particle phase; the melting point of the matrix phase is lower than that of the dispersed particle phase, and the dispersed particle phase is coated in the matrix phase; during the solidification process of the initial alloy melt, the impurity element D in the initial alloy melt is redistributed in the dispersed particle phase and the matrix phase, and is enriched in the matrix phase, so that the dispersed particle phase is purified;
[0010] The composition of the dispersed particle phase in the initial alloy strip is mainly (M x T y ) x1 D z1 , the average composition of the matrix phase is mainly Cu x2 D z2 ; and 99%≤x1≤100%, 0≤z1≤1%; 90%≤x2≤100%, 0≤z2≤10%; z1≤d≤z2, 2z1≤z2; x1, z1, x2, z2 represent the atomic percentage content of the corresponding constituent elements respectively;
[0011] Step S3, removing the matrix phase in the initial alloy strip, and retaining the dispersed particle phase that cannot be removed simultaneously during the matrix phase removal process; collecting the dispersed particle phase that has fallen off, that is, obtaining a high-purity target powder material containing precious metal elements composed of the original dispersed particles.
[0012] In the step S1,
[0013] Furthermore, M contains at least one of the noble metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, and Ag, and the atomic percentage content of the elements Ir, Ru, Re, Os, and Tc in M is higher than 50%;
[0014] Furthermore, the M contains at least one of the noble metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, and Ag, and the atomic percentage content of the elements Ir, Ru, Re, Os, and Tc in M is higher than 75%;
[0015] Preferably, M comprises at least one of the noble metal elements Ir, Ru, Re, Os, and Tc.
[0016] Furthermore, the T comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, and Fe, and the atomic percentage of W, Cr, Mo, V, Ta, Nb, etc. in T is higher than 50%;
[0017] Furthermore, the T comprises at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, and Fe, and the atomic percentage of W, Cr, Mo, V, Ta, Nb and other elements in T is higher than 75%;
[0018] Preferably, the T comprises at least one of W, Cr, Mo, V, Ta, and Nb;
[0019] Furthermore, the sources of the D impurity elements in the initial alloy melt include: impurities introduced by the initial alloy raw materials, and impurities introduced by the atmosphere or crucible during the smelting process. Among them, impurities introduced by the atmosphere refer to impurities such as O, N, and H in the ambient atmosphere absorbed by the alloy melt.
[0020] Further, D is an impurity element and includes at least one of O, H, N, P, S, F, Cl, I, and Br; and the total content of these impurity elements is the content of the D impurity element;
[0021] Furthermore, if the raw materials are simple substances or master alloys containing impurity elements, they can be melted according to the proportion to prepare the initial alloy melt. If the raw materials provided are directly alloy raw materials corresponding to the composition of the initial alloy melt, they can be remelted to obtain the initial alloy melt.
[0022] Furthermore, the combination of Cu and M, and Cu and T in the average composition of the initial alloy melt in step S1 is extremely important, and the selection principle is to ensure that no intermetallic compound is formed between Cu and M, and between Cu and T during the solidification of the alloy melt. In this way, the two-phase separation of the matrix phase dominated by Cu and the particle phase dominated by M and T can be achieved during the solidification of the initial alloy melt, which is beneficial to the subsequent preparation of a powder material containing precious metal elements dominated by M and T.
[0023] Furthermore, 59.9%≤a≤99.8%, 0.1%≤b≤40%, 0 <d≤5%;
[0024] In the step S2,
[0025] Furthermore, the initial alloy strip does not contain an intermetallic compound composed of Cu and M;
[0026] Furthermore, the initial alloy strip does not contain an intermetallic compound composed of Cu and T;
[0027] Furthermore, when M contains at least one of Au, Pt, Pd, and Ag, it is dissolved in the main component (M x T y ) x1 D z1 In the dispersed particle phase, the main component is (M x T y ) x1 D z1 The dispersed particle phase also contains at least one of Ir, Ru, Re, Os, and Tc belonging to M;
[0028] Furthermore, when T contains at least one of Zr, Hf, Ti, and Fe, it is dissolved in the main component (M x T y ) x1 D z1 In the dispersed particle phase, the main component is (M x T y ) x1 D z1 The dispersed particle phase also contains at least one of W, Cr, Mo, V, Ta, and Nb belonging to T;
[0029] Further, the components are mainly (M x T y ) x1 D z1 The dispersed particle phase containing the precious metal element does not contain the Cu element;
[0030] Furthermore, the alloy melt is solidified by a strip-spinning method and a continuous casting method. Generally speaking, a thinner initial alloy strip can be obtained by the strip-spinning method, while a thicker alloy strip can be obtained by the continuous casting method.
[0031] Whether it is the thin alloy strip obtained by the strip-spinning method or the thick alloy strip obtained by the continuous casting method, their morphology is completely different from that of the alloy ingots obtained by the ordinary casting method. The alloy ingots obtained by the ordinary casting method generally have no obvious difference in length, width and thickness in size.
[0032] Further, the thickness range of the initial alloy strip is 5μm to 10mm; further, the thickness range of the initial alloy strip is 5μm to 5mm; preferably, the thickness range of the initial alloy strip is 5μm to 1mm; further preferably, the thickness range of the initial alloy strip is 5μm to 200μm; further preferably, the thickness range of the initial alloy strip is 5μm to 20μm.
[0033] It should be noted that when the thickness of the initial alloy strip is at the millimeter level, it can also be called an alloy sheet.
[0034] Further, the width of the cross section of the initial alloy strip is more than 2 times its thickness; further, the length of the initial alloy strip is more than 10 times its thickness; preferably, the length of the initial alloy strip is more than 50 times its thickness; preferably, the length of the initial alloy strip is more than 100 times its thickness;
[0035] Furthermore, the solidification rate of the initial alloy melt is 1K / s to 10 7 K / s;
[0036] Furthermore, the particle size of the dispersed particle phase is related to the solidification rate of the initial alloy melt; generally speaking, the particle size of the dispersed particle phase is negatively correlated with the solidification rate of the initial alloy melt, that is, the greater the solidification rate of the initial alloy melt, the smaller the particle size of the dispersed particle phase.
[0037] Further, the particle size range of the dispersed particle phase is 2nm~3mm; further, the particle size range of the dispersed particle phase is 2nm~500μm; preferably, the particle size range of the dispersed particle phase is 2nm~99μm; further preferably, the particle size range of the dispersed particle phase is 2nm~5μm; further preferably, the particle size range of the dispersed particle phase is 2nm~200nm; further preferably, the particle size range of the dispersed particle phase is 2nm~100nm.
[0038] Furthermore, the solidification rate of the initial alloy melt is 10 5 K / s~10 7 K / s, dispersed particles with a particle size mainly in the nanometer scale can be obtained.
[0039] Furthermore, the solidification rate of the initial alloy melt is 10 4 K / s~10 5 K / s, dispersed particles with a particle size mainly in the submicron scale can be obtained.
[0040] Furthermore, the solidification rate of the initial alloy melt is 102 K / s~10 4 K / s, dispersed particles with a particle size mainly in the micron scale can be obtained.
[0041] Furthermore, the solidification rate of the initial alloy melt is 1K / s to 10 2 K / s, dispersed particles with a particle size mainly in the millimeter scale can be obtained.
[0042] Furthermore, the particle shape of the dispersed particle phase is not limited and may include at least one of dendrite, spherical, near-spherical, square, pie, and rod shapes; when the particle shape is rod-shaped, the size of the particle specifically refers to the diameter of the cross section of the rod.
[0043] Furthermore, when the dispersed particles are of nanometer or submicron scale, spherical or nearly spherical particles are obtained with a high probability; when the dispersed particles are of micron scale or above, dendritic particles are obtained with a high probability.
[0044] Furthermore, the dispersed particle phase solidifies and precipitates from the initial alloy melt. According to the nucleation and growth theory, whether it is the nearly spherical nanoparticles that have just nucleated and grown, or the fully grown micron-sized and millimeter-sized dendrite particles, their crystal growth has a fixed orientation relationship, so that the precipitated single particles are mainly composed of a single crystal.
[0045] When the volume percentage of the dispersed particles in the entire initial alloy strip is high, during the endogenous precipitation process of the single crystal particles, it is not ruled out that two or more particles merge. If two or more single crystal particles are only softly agglomerated, mutually adsorbed, or only a few parts are in contact and connected together, and are not fully combined into one particle through normal grain boundaries like polycrystalline materials, they are still two single crystal particles. Its characteristic is that after the matrix phase is removed in the subsequent process, these single crystal particles can be easily separated by technologies including ultrasonic dispersion treatment, air flow grinding, etc. Normal ductile metal or alloy polycrystalline materials are difficult to separate the grain boundaries by technologies including ultrasonic dispersion treatment, air flow grinding, etc.
[0046] Preferably, the number of single crystal particles in the dispersed particles in the initial alloy strip accounts for no less than 60% of the number of all dispersed particles.
[0047] As a further preference, the number of single crystal particles in the dispersed particles accounts for no less than 90% of the number of all dispersed particles.
[0048] Furthermore, for a certain initial alloy strip, the volume percentage of the dispersed particle phase in the initial alloy strip can be determined by calculating the corresponding initial alloy melt composition, dispersed particle phase composition, matrix phase composition, combined with element atomic weight, density parameters, etc.
[0049] Furthermore, the volume percentage content of the dispersed particle phase in its corresponding initial alloy strip is not higher than 50%.
[0050] Furthermore, 99% ≤ x1 < 100%, 0 < z1 ≤ 1%; 90% ≤ x2 < 100%, 0 < z2 ≤ 10%; z1 < d < z2, 2z1 < z2;
[0051] Furthermore, z1 < d < z2, and 3z1 < z2, that is, the content of D impurities in the dispersed particle phase is lower than that in the initial alloy melt, and three times the content of D impurities in the dispersed particle phase is still lower than that in the matrix phase;
[0052] Furthermore, 99.5% ≤ x1 < 100%, 0 < z1 ≤ 0.5%;
[0053] Furthermore, 99.8% ≤ x1 < 100%, 0 < z1 ≤ 0.2%;
[0054] In the step S3,
[0055] Furthermore, the method for removing the matrix phase in the alloy strip includes acid reaction removal;
[0056] Since Cu can generally be removed by corrosion with a relatively concentrated and high-temperature hydrochloric acid aqueous solution, while elements M and T generally do not react with a relatively concentrated and high-temperature hydrochloric acid aqueous solution. Even if element (such as Fe) in M can react with concentrated hydrochloric acid alone, when it is solid-solved in inert M or T, it is protected by inert M or T and cannot react with concentrated hydrochloric acid. Therefore, the matrix phase in the alloy strip can be removed by corrosion with a relatively concentrated and high-temperature hydrochloric acid aqueous solution while retaining the dispersed particle phase.
[0057] Furthermore, the concentration of the hydrochloric acid aqueous solution in the acid reaction removal method is 2 mol / L to 12 mol / L.
[0058] Furthermore, the temperature for the reaction of the hydrochloric acid aqueous solution with the alloy strip in the acid reaction removal method is 0°C to 100°C.
[0059] Furthermore, since the target powder material is the dispersed particle phase detached from the initial alloy strip, the composition, particle size, etc. of the target powder material are equivalent to those of the corresponding dispersed particle phase.
[0060] Furthermore, the particle size range of the target powder material containing precious metal elements is 2nm~3mm; preferably, the particle size range of the target powder material containing precious metal elements is 2nm~500μm; preferably, the particle size range of the target powder material containing precious metal elements is 2nm~99μm; further preferably, the particle size range of the target powder material containing precious metal elements is 2nm~5μm; further preferably, the particle size range of the target powder material containing precious metal elements is 2nm~200nm; further preferably, the particle size range of the target powder material containing precious metal elements is 2nm~100nm.
[0061] Furthermore, after the initial alloy strip reacts with the acid solution, the dispersed particles are separated from the initial alloy strip, and are cleaned and dried to obtain the target powder material containing the precious metal element.
[0062] Furthermore, the target powder material containing precious metal elements mainly comprises (M x T y ) x1 D z1 ;
[0063] Further, the components are mainly (M x T y ) x1 D z1 The target powder material containing the precious metal element does not contain the Cu element;
[0064] Preferably, the composition of the target powder material containing precious metal elements is (M x T y ) x1 D z1 ;
[0065] Furthermore, the atomic percentage content of the D impurity element in the target powder material containing the noble metal element does not exceed 1%;
[0066] Preferably, the atomic percentage content of the D impurity element in the target powder material containing the noble metal element does not exceed 0.5%;
[0067] Preferably, the atomic percentage content of the D impurity element in the target powder material containing the noble metal element does not exceed 0.2%;
[0068] Furthermore, after step S3, the following steps are further performed: after screening the target powder material containing the precious metal element, the target powder material containing the precious metal element with a particle size range of 5 μm to 200 μm is selected for plasma spheroidization treatment to obtain a spherical powder material containing the precious metal element;
[0069] Furthermore, the particle size of the spherical powder material containing precious metal elements ranges from 5 μm to 200 μm.
[0070] The present invention also relates to the application of the target powder material containing precious metal elements obtained by the above-mentioned preparation method or the spherical powder material containing precious metal elements in catalytic materials, powder metallurgy, composite materials, absorbing materials, sterilization materials, metal injection molding, 3D printing, and coatings.
[0071] Furthermore, the application of the spherical powder material containing precious metal elements obtained by the above preparation method in the field of metal powder 3D printing is characterized in that the particle size range of the spherical powder material containing precious metal elements is 10 μm to 200 μm.
[0072] Furthermore, the target powder material containing precious metal elements or the spherical powder material containing precious metal elements obtained by the above preparation method is used in metal injection molding and powder metallurgy, characterized in that the particle size range is 0.1 μm to 200 μm.
[0073] Furthermore, the target powder material containing precious metal elements obtained by the above preparation method is used in coatings and catalysts, characterized in that the particle size range of the powder material is 2 nm to 5 μm.
[0074] The present invention also relates to an alloy strip, characterized in that it comprises endogenous powder and a coating; the solidified structure of the alloy strip comprises a matrix phase and a dispersed particle phase, the matrix phase is the coating, and the dispersed particle phase is the endogenous powder; the coating has a lower melting point than the endogenous powder, and the endogenous powder is coated in the coating;
[0075] The components of the raw powder in the initial alloy strip are mainly (M x T y ) x1 D z1 The average composition of the coating is mainly Cu x2 D z2 ; and 99%≤x1≤100%, 0≤z1≤1%; 90%≤x2≤100%, 0≤z2≤10%; z1≤d≤z2, 2z1≤z2; x1, z1, x2, z2 represent the atomic percentage content of the corresponding constituent elements respectively;
[0076] Preferably, further, 99% ≤ x1 < 100%, 0 < z1 ≤ 1%; 90% ≤ x2 < 100%, 0 < z2 ≤ 10%; z1 < d < z2, 2z1 < z2;
[0077] Further, z1 < d < z2, and 3z1 < z2,
[0078] Preferably, 99.5% ≤ x1 < 100%, 0 < z1 ≤ 0.5%;
[0079] More preferably, 99.8% ≤ x1 < 100%, 0 < z1 ≤ 0.2%;
[0080] Further, M contains at least one of noble metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, Ag; Preferably, M contains at least one of noble metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, Ag, and the atomic percentage content of elements such as Ir, Ru, Re, Os, Tc in M is higher than 50%; More preferably, M contains at least one of noble metal elements Ir, Ru, Re, Os, Tc;
[0081] Further, T contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe; Preferably, T contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, and the atomic percentage content of elements such as W, Cr, Mo, V, Ta, Nb in T is higher than 50%; More preferably, T contains at least one of W, Cr, Mo, V, Ta, Nb;
[0082] Wherein, D is an impurity element and contains at least one of O, H, N, P, S, F, Cl, I, Br; and the total content of these impurity elements is the content of D impurity elements;
[0083] Further, the main component is (M x T y ) x1 D z1 The endogenous powder in the alloy strip does not contain Cu element;
[0084] Preferably, the composition of the endogenous powder in the starting alloy strip is (M x T y ) x1 D z1 , and the average composition of the coating is Cu x2 D z2 ;
[0085] Further, the thickness range of the alloy strip is 5μm to 10mm; preferably, the thickness range of the alloy strip is 5μm to 5mm; preferably, the thickness range of the alloy strip is 5μm to 1mm; further preferably, the thickness range of the alloy strip is 5μm to 200μm; further preferably, the thickness range of the alloy strip is 5μm to 20μm.
[0086] Further, the width of the cross-section of the alloy strip is more than twice its thickness; further, the length of the initial alloy strip is more than 10 times its thickness; preferably, the length of the initial alloy strip is more than 50 times its thickness; preferably, the length of the initial alloy strip is more than 100 times its thickness.
[0087] Further, the particle size range of the endogenous powder is 2nm~3mm; preferably, the particle size range of the endogenous powder is 2nm~500μm; preferably, the particle size range of the endogenous powder is 2nm~99μm; further preferably, the particle size range of the endogenous powder is 2nm~10μm; further preferably, the particle size range of the endogenous powder is 2nm~1μm; further preferably, the particle size range of the endogenous powder is 2nm~200nm; further preferably, the particle size range of the endogenous powder is 2nm~100nm.
[0088] Furthermore, the shape of the endogenous powder includes at least one of a dendrite shape, a sphere shape, a nearly spherical shape, a square shape, a cake shape, and a rod shape.
[0089] Furthermore, the number of single crystal particles in the endogenous powder in the alloy strip accounts for no less than 60% of the total number of endogenous powder.
[0090] Furthermore, the volume percentage of the endogenous powder in the alloy strip does not exceed 50%.
[0091] Furthermore, the alloy strip is prepared by step S1 and step S2 in the above-mentioned method for preparing a powder material containing precious metal elements.
[0092] It should be noted that the M, T or D in the solution of the present invention may also contain other elements or impurity elements other than the above-listed elements. As long as the introduction of these elements or the change in the content does not cause a "qualitative change" in the initial alloy solidification process and law, it will not affect the implementation of the above technical solution of the present invention.
[0093] Specifically, the result that the initial alloy solidification process and law do not undergo "qualitative change" means that when the M, T or D contains other elements or impurity elements other than the above-listed elements, the following facts, processes and laws listed in 1)-3) still exist:
[0094] 1) The initial alloy strip does not contain intermetallic compounds mainly composed of Cu and M, or Cu and T;
[0095] 2) The solidified structure of the initial alloy strip includes a matrix phase and a dispersed particle phase; the melting point of the matrix phase is lower than that of the dispersed particle phase, and the dispersed particle phase is coated in the matrix phase;
[0096] 3) When the D impurity content in the initial alloy melt is not 0, the D impurity content in the dispersed particle phase is lower than the D impurity content in the initial alloy melt, and twice the D impurity content in the dispersed particle phase is still lower than the D impurity content in the matrix phase.
[0097] The technical solution of the present invention has the following beneficial effects:
[0098] First, through clever alloy design, phase separation occurs when the initial alloy melt solidifies, so that endogenous particles of a certain particle size target component can be formed during the solidification process of the initial alloy melt and can be separated through subsequent processes. Generally speaking, nano metal particles can be prepared relatively easily through bottom-up chemical methods, such as chemical reduction, but when the scale of the particles increases to hundreds of nanometers or even micrometers, it is difficult to prepare. Through top-down physical methods, such as atomization, ball milling, etc., metal particles of tens or hundreds of microns can be prepared relatively easily, but when the scale of the particles is reduced to hundreds of nanometers to several microns, it is also difficult to prepare. The technical solution of the present invention can easily prepare nano-scale, submicron-scale, micron-scale, and even millimeter-scale target metal powder particles according to the different cooling rates during the solidification of the initial alloy strip, breaking through the above-mentioned technical difficulties and having great advantages.
[0099] Secondly, it is achieved that high-purity target powder materials are obtained through low-purity raw materials, and a new way is pointed out for preparing high-purity powder materials from low-purity raw materials, which has positive significance. The improvement of the purity of the target powder material of the present invention is mainly achieved through the following three mechanisms: 1) The "absorption" effect of the relatively active matrix main element Cu on the impurity elements of the initial alloy melt. Since Cu in the alloy is a low-melting-point element, it has a stronger affinity with the impurity element D during the melting and solidification process of the alloy melt, which can make the impurity element D in the initial alloy melt enter more into the matrix phase mainly composed of Cu elements; 2) During the nucleation and growth process of the endogenously precipitated dispersed particle phase, the impurity element D will be discharged into the remaining melt. As long as the endogenously precipitated dispersed particle phase is not later than the matrix phase during the solidification process, its impurities will be enriched in the part of the melt that solidifies last, that is, the part of the melt that is mainly composed of the main elements of the matrix phase and solidifies to form the matrix phase. 3) Due to the existence of the matrix phase, the crucible-related impurities that enter the melt due to the interaction between the crucible and the melt during the smelting process are generally concentrated in the matrix phase, thereby further ensuring the purity of the dispersed particle phase. This further reduces the requirements for the crucible during the smelting process and greatly reduces the production cost.
[0100] Third, a target metal powder mainly composed of single crystal particles can be obtained. Compared with polycrystalline powder, single crystal powder can obtain many significant and beneficial effects. During the solidification process of the initial alloy melt, each endogenous dispersed particle is nucleated at a certain position in the melt and grows up according to a specific atomic arrangement. By controlling the volume percentage of the dispersed particle phase in the initial alloy strip not exceeding 50%, it is ensured that each endogenous particle can be dispersedly distributed, and it is difficult for each endogenous particle to merge and grow. Therefore, most of the dispersed particle phases finally obtained are single crystal phases. Even if the scale is as large as tens of microns or millimeters, the growth direction of each secondary dendrite maintains a certain phase relationship with the growth direction of the main dendrite, and it still belongs to a single crystal particle. For polycrystalline materials, their grain boundaries are generally prone to contain impurity elements discharged from the crystal during solidification, so it is difficult to obtain high-purity polycrystalline powder materials. When the target metal powder is mainly composed of single crystal particles, its purity must be guaranteed. Moreover, the atoms on the surface of single crystal particles have specific arrangements, such as (111) plane arrangement, etc. These specific arrangements will give the target metal powder special mechanical, physical and chemical properties, thereby producing beneficial effects.
[0101] Fourth, the alloy strip composed of endogenous powder and coating (matrix phase) creatively uses the in-situ generated matrix phase to wrap the endogenous powder, thereby maintaining the high purity and high activity of the endogenous powder. Specifically, metal or alloy powders prepared by traditional chemical methods or physical methods, especially nanopowders with a very large specific surface area, are extremely easy to oxidize naturally and face the problem of difficult powder preservation. In response to this problem, after the technical solution involved in the present invention prepares the alloy strip composed of endogenous metal powder and coating (matrix phase), it is not necessary to remove the coating in a hurry, but to directly use the coating to protect the endogenous metal powder from being naturally oxidized. This alloy strip composed of endogenous metal powder and coating can be directly used as a raw material for downstream production, and therefore has the potential to become a special type of product. When high-purity powder is required for downstream production, the endogenous metal powder can be released from the coating in the alloy strip at the right time and under the right environment according to the characteristics of the next process, and then the released endogenous powder can enter the next production process in the shortest possible time, thereby greatly reducing the chance of the endogenous metal powder being contaminated by impurities such as oxygen. For example, when the endogenous metal powder is a nanopowder, the endogenous metal powder can be compounded with the resin at the same time as it is released from the coating or immediately thereafter, thereby preparing a resin-based composite material with high activity endogenous metal powder added thereto.
[0102] Fifth, the solid alloy obtained by solidification in the step S2 is strip-shaped, which ensures the uniformity of the product shape and the feasibility of large-scale production. When the alloy strip is a thin alloy strip, it can be prepared by the strip-throwing method, as long as the flow rate of the alloy melt to the rotating roller is maintained to be fixed, the rotating speed of the rotating roller is fixed, and the alloy thin strip with uniform thickness can be obtained, and the preparation process can be carried out continuously, which is conducive to large-scale production. When the alloy strip is a thick alloy strip, it can be prepared by a mature continuous casting method, and the principle of continuous casting is similar to the principle of the strip-throwing method, and a continuous and uniform thick strip can also be obtained by the melt, and the preparation process can also be carried out continuously, which is conducive to large-scale production. When the thickness of the alloy strip is uniform, the cooling rate is also relatively uniform, and the dispersed particle size is also relatively uniform. In comparison, if the solid alloy obtained by solidification is ingot-shaped, according to common sense, the ingot does not have uniform thickness, and there is no obvious length and endpoint, which generally causes the internal melt to dissipate heat. It is easy to obtain abnormally large endogenous particles, and only when it is simply necessary to collect large endogenous particles and purify them, it is necessary to operate like this. Moreover, ordinary ingots are difficult to produce continuously. Therefore, the present invention obtains alloy strips by solidification, which are suitable for subsequent preparation of powder materials by "dephasing method".
[0103] Therefore, the preparation method of the present invention has the characteristics of simple process, easy operation and low cost. It can prepare a variety of high-purity powder materials containing precious metal elements including nanometer, submicron and micron levels, and has good application prospects in the fields of catalytic materials, powder metallurgy, composite materials, absorbing materials, sterilization materials, metal injection molding, 3D printing, coatings, etc.
[0104] As an alternative, the present invention also provides a method for preparing metal powder, which comprises the following steps:
[0105] Step 1: Select the composition as Cu a M b T c wherein M is selected from at least one of Ir, Ru, Re, Os and Tc, and T is selected from at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti and Fe; a, b and c represent the atomic percentage content of the corresponding constituent elements, and 50%≤a≤99.9%, 0.1%≤b≤50%, 0≤c≤49.9%, and a+b+c=100%; the initial alloy raw materials are melted according to the initial alloy component ratio to obtain a uniform alloy melt, and then the alloy melt is solidified into Cu by a rapid solidification technique. a M b T c Master alloy; the Cu a M b T c The solidified structure of the master alloy consists of a matrix phase with a composition of Cu and a dispersed particle phase with a composition of MT, and the melting point of the MT dispersed particle phase is higher than the melting point of the Cu matrix phase; preferably, 0.2%≤b≤50%, c=0, a+b+c=100%;
[0106] Step 2: The Cu a M b T c The Cu matrix phase in the master alloy is removed by acid solution reaction, while the MT dispersed particle phase that does not react with the acid solution is retained, so that the target metal powder composed of the MT dispersed particle phase is obtained.
[0107] The above technical solution can realize the preparation of ultrafine metal powder. The higher the solidification rate of the master alloy melt, the smaller the dispersed particle phase in the obtained master alloy solidification structure. Therefore, the present invention can obtain nano-scale, submicron-scale, and micron-scale dispersed particle phases respectively by controlling the size of the solidification rate, and then obtain the target metal powder of the corresponding particle size by removing the Cu matrix phase, which greatly reduces the preparation cost of ultrafine metal powder.
[0108] Furthermore, the rapid solidification technology includes a metal roller strip method for alloy melt, and the solidification rate of the alloy melt is 100K / s to 1×10 7 K / s.
[0109] Furthermore, the rapid solidification technology includes an alloy melt atomization powder making method, and the solidification rate of the alloy melt is 50K / s to 5×10 5 K / s.
[0110] Furthermore, for the initial alloy composition, when the solidification rate is higher than 5×10 4 K / s, a dispersed particle phase of nanometer scale (2nm~200nm) can be obtained; when the solidification rate is 1×10 3 K / s~5×10 4 K / s, a submicron (200nm~1000nm) dispersed particle phase can be obtained; when the solidification rate is lower than 1×10 3 K / s, a dispersed particle phase of micrometer size (>1μm) can be obtained.
[0111] Furthermore, the Cu a M b T c The master alloy has at least one dimension in the three-dimensional dimension range of 5μm to 500μm. When the strip master alloy is prepared by the metal roller stripping method, the thickness of the master alloy strip is 5μm to 500μm; when the powder master alloy is prepared by the melt atomization powder making technology, the diameter of the master alloy powder is 5μm to 500μm.
[0112] Furthermore, the atomization powder making technology includes at least one of gas atomization, water atomization, water-vapor-combined atomization, and vacuum atomization.
[0113] Furthermore, the shape of the dispersed particle phase in the solidified structure of the master alloy includes at least one of a dendrite shape, a sphere, a nearly spherical shape, a square shape, a cake shape, and a rod shape, and the particle size ranges from 2 nm to 100 μm.
[0114] Furthermore, the acid solution includes at least one of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, perchloric acid, acetic acid, and oxalic acid. The ratio and concentration of the acid are determined to ensure that the Cu matrix can be removed by reaction, while the MT dispersed particle phase does not react with the acid. Since the MT dispersed particle phase is mainly composed of extremely acid-resistant elements, and Cu can react significantly with certain acids, such as 2 mol / L hydrochloric acid aqueous solution with a concentration higher than , it is possible to achieve the removal of the Cu matrix phase by designing a suitable acid solution ratio and concentration based on the specific composition and ratio of the intermediate alloy, while retaining the MT dispersed particle phase. When MT contains Fe, due to the protective effect of extremely acid-resistant M or other T elements, Fe is difficult to react with acid and be removed. Therefore, it is also feasible to prepare MT metal powder containing Fe.
[0115] Furthermore, the particle size of the target metal powder composed of dispersed particle phase ranges from 2 nm to 100 μm.
[0116] Furthermore, the shape of the target metal powder includes at least one of a dendrite shape, a sphere shape, a nearly spherical shape, a cube shape, a pie shape, and a rod shape.
[0117] The technical features of the present invention are further described in detail below:
[0118] First, the present invention can obtain nano-scale, submicron-scale, and micron-scale dispersed particle phases by controlling the size of the melt solidification rate, and then obtain the target metal powder of the corresponding particle size by removing the matrix phase, which greatly reduces the preparation cost of ultrafine metal powder.
[0119] Secondly, when the Cu a M b T c When MT in the alloy is a combination of multiple elements, the resulting dispersed particle phase is also composed of multiple elements, which makes it easier and more feasible to prepare the target alloy powder composed of the dispersed particle phase, greatly expanding the composition range and application field of the target alloy powder.
[0120] Therefore, the preparation method of the alternative invention has the characteristics of simple process, easy operation and low cost. It can prepare a variety of metal powders including nanometer, submicron and micron levels, and has good application prospects in the fields of catalysis, powder metallurgy, composite materials, etc. DETAILED DESCRIPTION
[0121] Hereinafter, the method for preparing the high-purity metal powder will be further described through the following specific examples.
[0122] Example 1
[0123] This embodiment provides a method for preparing nano-Ru powder, which comprises the following steps:
[0124] The atomic ratio formula is Cu 90 Ru 10 The raw materials are weighed according to the formula, and the initial alloy raw materials are melted uniformly and then 10 6 The solidification rate of K / s was used to prepare a Cu film with a thickness of 15 μm. 90 Ru 10 The solidified structure of the alloy strip is composed of a matrix phase with a component of Cu and a dispersed particle phase with a large amount of component of Ru, wherein the Ru particles are nearly spherical in shape and have a particle size range of 3nm to 150nm.
[0125] The Cu matrix in the master alloy strip is removed by reaction with 6 mol / L hydrochloric acid aqueous solution, so that the Ru particles in the master alloy strip that are difficult to react with the hydrochloric acid aqueous solution of this concentration are separated, and nano-Ru powder is obtained, and its particle size ranges from 3nm to 150nm.
[0126] Example 2
[0127] This embodiment provides a method for preparing nano-Ru powder, which comprises the following steps:
[0128] The atomic ratio formula is Cu 95 The raw materials were weighed according to the formula, and the initial alloy raw materials were melted uniformly. The alloy melt was atomized by gas atomization technology at a rate of 5×10 4 K / s solidification rate to prepare Cu with particle size ranging from 5μm to 100μm 95 Ru5 master alloy powder. The solidified structure of the master alloy powder consists of a matrix phase with a component of Cu and a dispersed particle phase with a large amount of component of Ru, wherein the Ru dispersed particles are nearly spherical in shape and have a particle size range of 50nm to 200nm.
[0129] The Cu matrix in the master alloy powder is removed by reaction with a 6 mol / L hydrochloric acid aqueous solution, so that Ru particles in the master alloy powder that are difficult to react with the hydrochloric acid aqueous solution of this concentration are separated, and nano-Ru powder is obtained, and its particle size ranges from 50nm to 200nm.
[0130] Example 3
[0131] This embodiment provides a method for preparing submicron Ir-Nb powder, which comprises the following steps:
[0132] The atomic ratio formula is Cu 70 Ir 15 Nb 15The raw materials are weighed according to the formula, the initial alloy raw materials are melted uniformly, and the alloy melt is atomized by gas atomization technology at a rate of 10 4 K / s solidification rate to prepare Ir with particle size ranging from 10μm to 150μm 50 Nb 50 The solidification structure of the intermediate alloy powder is composed of a matrix phase with a composition of Cu and a large amount of Ir 50 Nb 50 The dispersed particle phase consists of Ir 50 Nb 50 The shape of the dispersed particles is nearly spherical, and the particle size ranges from 50nm to 1000nm.
[0133] The Cu matrix in the master alloy powder is removed by reaction with a 6 mol / L hydrochloric acid aqueous solution, so that the Ir in the master alloy powder which is difficult to react with the hydrochloric acid aqueous solution of this concentration is 50 Nb 50 The particles are separated and submicron Ir is obtained. 50 Nb 50 The powder has a particle size range of 50nm to 1000nm.
[0134] Example 4
[0135] This embodiment provides a method for preparing nano Ru-Ir-Os-Fe powder, which comprises the following steps:
[0136] The atomic ratio formula is Cu 90 Ru 2.5 Ir 2.5 Os 2.5 Fe 2.5 The raw materials are weighed according to the formula, and the initial alloy raw materials are melted uniformly and then 10 6 The solidification rate of K / s was used to prepare a Cu film with a thickness of 15 μm. 90 Ru 2.5 Ir 2.5 Os 2.5 Fe 2.5 The solidification structure of the alloy strip is composed of a matrix phase with a composition of Cu and a large amount of Ru. 25 Ir 25 Os 25 Fe 25 The dispersed particle phase consists of Ru 25 Ir 25 Os 25 Fe 25 The shape of the particles is nearly spherical, and the particle size ranges from 3nm to 150nm.
[0137] The Cu matrix in the master alloy strip is removed by reaction with a 5 mol / L hydrochloric acid aqueous solution, so that the Ru in the master alloy strip which is difficult to react with the hydrochloric acid aqueous solution of this concentration is 25 Ir 25 Os 25 Fe 25 The particles are separated and nano-Ru 25 Ir 25 Os 25 Fe 25 The powder has a particle size range of 3nm to 150nm.
[0138] Example 5
[0139] This embodiment provides a method for preparing submicron W-Re powder, which comprises the following steps:
[0140] The atomic ratio formula is Cu 90 W5Re5 alloy, weigh the raw materials according to the formula, melt the initial alloy raw materials evenly, and then use the copper roller stripping technology to 4 K / s solidification rate to prepare a Cu with a thickness of 150 μm 90 W5Re5 master alloy strip. The solidification structure of the alloy strip is composed of a matrix phase with a composition of Cu and a large amount of W 50 Re 50 The dispersed particle phase consists of Ru 25 Ir 25 Os 25 Fe 25 The shape of the particles is nearly spherical, and the particle size ranges from 50nm to 1000nm.
[0141] The Cu matrix in the master alloy strip was removed by reaction with a 6 mol / L hydrochloric acid aqueous solution, so that the W in the master alloy strip which was difficult to react with the hydrochloric acid aqueous solution of this concentration 50 Re 50 The particles are separated and submicron W is obtained. 50 Re 50 The powder has a particle size range of 50nm to 1000nm.
[0142] Example 6
[0143] This embodiment provides a method for preparing micron Ir-Ta-Nb-V powder, the preparation method comprising the following steps:
[0144] The atomic ratio formula is Cu 80 The raw materials of Ir5Ta5Nb5V5 alloy were weighed according to the formula, and the initial alloy raw materials were melted uniformly, and then a Cu film with a thickness of 500 μm was prepared at a solidification rate of 500 K / s by copper roller spinning technology.80 Ir5Ta5Nb5V5 master alloy strip. The solidification structure of the alloy strip is composed of a matrix phase with a composition of Cu and a large amount of Ir 25 Ta 25 Nb 25 V 25 The dispersed particle phase consists of Ir 25 Ta 25 Nb 25 V 25 The particle shape is dendrite-shaped, and the particle size ranges from 1 μm to 50 μm.
[0145] The Cu matrix in the master alloy strip was removed by reaction with a 6 mol / L hydrochloric acid aqueous solution, so that the Ir in the master alloy strip which was difficult to react with the hydrochloric acid aqueous solution of this concentration 25 Ta 25 Nb 25 V 25 The particles are separated and micron Ir is obtained. 25 Ta 25 Nb 25 V 25 The powder has a particle size range of 1μm to 50μm.
[0146] Example 7
[0147] This embodiment provides a method for preparing nano Ir-Ta-Nb-Cr-Zr powder, which comprises the following steps:
[0148] The atomic ratio formula is Cu 75 The raw materials are weighed according to the formula, and the initial alloy raw materials are melted uniformly and then spun by copper roller strip technology at 10 6 The solidification rate of K / s was used to prepare a Cu film with a thickness of 15 μm. 75 Ir6Ta6Nb6Cr6Zr1 master alloy strip. The solidification structure of the alloy strip is composed of a matrix phase with a composition of Cu and a large amount of Ir 24 Ta 24 Nb 24 Cr 24 The dispersed particle phase of Zr4 is composed of Ir 24 Ta 24 Nb 24 Cr 24 The shape of Zr4 particles is nearly spherical, and the particle size ranges from 3nm to 150nm.
[0149] The Cu matrix in the master alloy strip was removed by reaction with a 5 mol / L hydrochloric acid aqueous solution, so that the Ir in the master alloy strip which was difficult to react with the hydrochloric acid aqueous solution of this concentration 24 Ta24 Nb 24 Cr 24 Zr4 particles are separated to obtain nano-Ir 24 Ta 24 Nb 24 Cr 24 Zr4 powder, the particle size range is 3nm~150nm.
[0150] Example 8
[0151] This embodiment provides a method for preparing nano Ir-Nb powder, which comprises the following steps:
[0152] Select Cu, Ir and Nb raw materials with atomic percentage contents of impurity elements of 0.2 at.%, 0.5 at.%, and 0.5 at.% respectively in D (including O, H, N, P, S, F, Cl, Br, and I), melt the raw materials in a molar ratio of Cu:Ir:Nb of about 70:15:15, and obtain Cu 69.9 Ir 14.9 Nb 14.9 D 0.3 of a homogeneous initial alloy melt.
[0153] Through the copper roller belt spinning technology, about ~10 6 The initial alloy melt was prepared into a Cu layer with a thickness of 20 μm at a solidification rate of K / s. 69.9 Ir 14.9 Nb 14.9 D 0.3 Alloy strip. The solidification structure of the alloy strip is mainly composed of Cu in atomic percentage. 99.6 D 0.4 The matrix phase and the bulk component are mainly Ir 49.97 Nb 49.97 D 0.06 The dispersed particle phase of Ir 49.97 Nb 49.97 D 0.06 The shape of the dispersed particles is nearly spherical, and the particle size ranges from 10nm to 150nm. 49.97 Nb 49.97 D 0.06 The volume percentage of dispersed particles in the alloy strip is about 37%;
[0154] The 4 mol / L hydrochloric acid solution was reacted with Cu 69.9 Ir 14.9 Nb 14.9 D 0.3 Alloy strip, the Cu matrix in the alloy strip is corroded and removed to obtain Ir 49.97 Nb49.97 D 0.06 Dispersed particles, the particle size range is 10nm ~ 150nm. And nano Ir 49.97 Nb 49.97 D 0.06 The total content of O, H, N, P, S, F, Cl, Br and I is 0.06 at.%.
[0155] Example 9
[0156] This embodiment provides a method for preparing nano Ir-Pt powder, which comprises the following steps:
[0157] Select Cu, Ir and Pt raw materials with atomic percentage contents of impurity elements of 0.2 at.%, 0.5 at.%, and 0.5 at.%, respectively, and melt the raw materials according to the molar ratio of Cu:Ir:Pt of about 70:20:10 to obtain Cu, Ir and Pt raw materials with atomic percentage contents of 0.2 at.%, 0.5 at.%, and 0.5 at.%, respectively. 69.85 Ir 19.9 Pt 9.95 D 0.3 of a homogeneous initial alloy melt.
[0158] Through the copper roller belt spinning technology, about ~10 6 The initial alloy melt was prepared into a Cu layer with a thickness of 20 μm at a solidification rate of K / s. 69.85 Ir 19.9 Pt 9.95 D 0.3 Alloy strip. The solidification structure of the alloy strip is mainly composed of Cu in atomic percentage. 99.6 D 0.4 The matrix phase and the bulk component are mainly Ir 66.62 Pt 33.31 D 0.07 The dispersed particle phase of Ir 66.62 Pt 33.31 D 0.07 The shape of the dispersed particles is nearly spherical, and the particle size ranges from 10nm to 150nm. 66.62 Pt 33.31 D 0.07 The volume percentage of dispersed particles in the alloy strip is about 34%;
[0159] The 4 mol / L hydrochloric acid solution was reacted with Cu 69.85 Ir 19.9 Pt 9.95 D 0.3 Alloy strip, the Cu matrix in the alloy strip is corroded and removed to obtain Ir 66.62 Pt 33.31 D0.07 Dispersed particles, the particle size range is 10nm ~ 150nm. And nano Ir 66.62 Pt 33.31 D 0.07 The total content of O, H, N, P, S, F, Cl, Br and I is 0.07 at.%.
[0160] Example 10
[0161] This embodiment provides a method for preparing nano Ir-Nb powder, which comprises the following steps:
[0162] The raw materials of Cu, Ir and Nb with atomic percentage contents of impurity elements of D (including O, H, N, P, S, F, Cl, Br, I) of 0.2 at.%, 0.5 at.%, and 0.5 at.% respectively are selected, wherein the Ir raw material also contains 2 at.% Rh. The raw materials are melted according to the molar ratio of Cu:Ir:Nb of about 70:15:15, and the atomic percentage composition is mainly Cu 69.9 (Ir 98 Rh2) 14.9 Nb 14.9 D 0.3 of a homogeneous initial alloy melt.
[0163] Through the copper roller belt spinning technology, about ~10 6 The initial alloy melt was prepared into a Cu layer with a thickness of 20 μm at a solidification rate of K / s. 69.9 (Ir 98 Rh2) 14.9 Nb 14.9 D 0.3 Alloy strip. The solidification structure of the alloy strip is mainly composed of Cu in atomic percentage. 99.6 D 0.4 The matrix phase and the bulk components are mainly (Ir 98 Rh2) 49.97 Nb 49.97 D 0.06 The dispersed particle phase is composed of (Ir 98 Rh2) 49.97 Nb 49.97 D 0.06 The shape of the dispersed particles is nearly spherical, and the particle size ranges from 10nm to 150nm. 98 Rh2) 49.97 Nb 49.97 D 0.06The volume percentage of dispersed particles in the alloy strip is about 37%; moreover, the introduction of a small amount of Rh in the alloy melt does not lead to the formation of intermetallic compounds composed of Cu and Rh in the initial alloy strip; and does not affect the structural characteristics of the matrix phase and the dispersed particle phase in the alloy strip, nor does it affect the law of reducing the impurity content in the dispersed particle phase.
[0164] The 4 mol / L hydrochloric acid solution was reacted with Cu 69.9 (Ir 98 Rh2) 14.9 Nb 14.9 D 0.3 Alloy strip, the Cu matrix in the alloy strip is corroded and removed to obtain (Ir 98 Rh2) 49.97 Nb 49.97 D 0.06 Dispersed particles, the particle size range is 10nm ~ 150nm. And nanometer (Ir 98 Rh2) 49.97 Nb 49.97 D 0.06 The total content of O, H, N, P, S, F, Cl, Br and I is 0.06 at.%.
[0165] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0166] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a powder material containing precious metal elements, characterized in that: The following steps are involved: Step 1: Select the initial alloy raw materials, melt the initial alloy raw materials according to the initial alloy composition ratio to obtain a uniform initial alloy melt containing impurity element D; the average composition of the initial alloy melt is mainly Cu a (M x T y ) b D d , where M contains at least one of noble metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, Ag, T contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe, and D contains at least one of O, H, N, P, S, F, Cl, I, Br; and 60% ≤ a < 99.9%, 0.1% ≤ b ≤ 40%, 0 < d ≤ 5%; 0.1% ≤ x ≤ 100%, 0% ≤ y ≤ 99.9%; where a, b, d, and x, y respectively represent the atomic percentage contents of the corresponding constituent elements; Step 2, solidifying the initial alloy melt into an initial alloy strip; the solidified structure of the initial alloy strip includes a matrix phase and a dispersed particle phase; the melting point of the matrix phase is lower than that of the dispersed particle phase, and the dispersed particle phase is coated in the matrix phase; during the solidification process of the initial alloy melt, the impurity element D in the initial alloy melt is redistributed in the dispersed particle phase and the matrix phase, and is enriched in the matrix phase, so that the dispersed particle phase is purified; The composition of the dispersed particle phase in the initial alloy strip is mainly (M x T y ), and the average composition of the matrix phase is mainly Cu x1 D z1 . And 99% ≤ x1 < 100%, 0 < z1 ≤ 1%; 90% ≤ x2 < 100%, 0 < z2 ≤ 10%; z1 < d < z2, 2z1 < z2; x1, z1, x2, z2 respectively represent the atomic percentage contents of the corresponding constituent elements; Step three, removing the matrix phase in the initial alloy strip, and retaining the dispersed particle phase that cannot be removed simultaneously during the matrix phase removal process; collecting the dispersed particle phase that has fallen off, that is, obtaining a high-purity target powder material composed of the original dispersed particles and containing precious metal elements.
2. The method for preparing a powder material containing a noble metal element according to claim 1, characterized in that: The sources of the D impurity elements in the initial alloy melt include: impurities introduced into the initial alloy raw materials, and impurities introduced into the atmosphere or crucible during the smelting process.
3. The method for preparing a powder material containing precious metal elements according to claim 1, characterized in that: The M contains at least one of the precious metal elements Ir, Ru, Re, Os, Tc, Au, Pt, Pd, and Ag, and the atomic percentage of elements such as Ir, Ru, Re, Os, and Tc in M is higher than 50%; the T contains at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, and Fe, and the atomic percentage of elements such as W, Cr, Mo, V, Ta, and Nb in T is higher than 50%.
4. The method for preparing a powder material containing precious metal elements according to claim 1, characterized in that: The initial alloy strip does not contain an intermetallic compound composed of Cu and M, nor does it contain an intermetallic compound composed of Cu and T.
5. The method for preparing a powder material containing precious metal elements according to claim 1, characterized in that: The number of single crystal particles of the dispersed particles in the initial alloy strip accounts for no less than 60% of the number of all dispersed particles.
6. The method for preparing a powder material containing precious metal elements according to claim 1, characterized in that: In step three, the method of removing the matrix phase in the initial alloy strip includes acid reaction removal.
7. The method for preparing a powder material containing precious metal elements according to claim 1, characterized in that: The particle size of the target powder material containing precious metal elements ranges from 2nm to 3mm.
8. The method for preparing a powder material containing precious metal elements according to claim 1, characterized in that: After step three, the following steps are further performed: after screening the target powder material containing precious metal elements, powder materials with a particle size range of 5 μm to 200 μm are selected for plasma spheroidization treatment to obtain spherical powder materials containing precious metal elements.
9. Use of the target powder material containing noble metal elements or the spherical powder material containing noble metal elements according to any one of claims 1 to 8 in catalytic materials.
10. Use of the target powder material containing precious metal elements or the spherical powder material containing precious metal elements according to any one of claims 1 to 8 in powder metallurgy.
11. Use of the target powder material containing noble metal elements or the spherical powder material containing noble metal elements according to any one of claims 1 to 8 in a composite material.
12. Use of the target powder material containing noble metal elements or the spherical powder material containing noble metal elements according to any one of claims 1 to 8 in a microwave absorbing material.
13. Use of the target powder material containing precious metal elements or the spherical powder material containing precious metal elements according to any one of claims 1 to 8 in a sterilization material.
14. Use of the target powder material containing noble metal elements or the spherical powder material containing noble metal elements according to any one of claims 1 to 8 in magnetic materials.
15. Use of the target powder material containing noble metal elements or the spherical powder material containing noble metal elements according to any one of claims 1 to 8 in metal injection molding.
16. Use of the target powder material containing precious metal elements or the spherical powder material containing precious metal elements according to any one of claims 1 to 8 in 3D printing.
17. Use of the target powder material containing noble metal elements or the spherical powder material containing noble metal elements according to any one of claims 1 to 8 in coatings.
18. An alloy strip, characterized in that: It includes endogenic powder and a coating body; the solidification structure of the alloy strip includes a matrix phase and a dispersed particle phase, the matrix phase is the coating body, and the dispersed particle phase is the endogenic powder; the melting point of the coating body is lower than that of the endogenic powder, and the endogenic powder is coated in the coating body; the main component of the endogenic powder in the alloy strip is (M x T y ) x1 D z1 , and the average composition of the coating body is mainly Cu x2 D z2 ; and 99% ≤ x1 < 100%, 0 < z1 ≤ 1%; 90% ≤ x2 < 100%, 0 < z2 ≤ 10%; z1 < d < z2, 2z1 < z2; x1, z1, x2, z2 respectively represent the atomic percentage contents of the corresponding constituent elements; wherein, the M includes at least one of Ir, Ru, Re, Os, Tc, Au, Pt, Pd, Ag; the T includes at least one of W, Cr, Mo, V, Ta, Nb, Zr, Hf, Ti, Fe; the D includes at least one of O, H, N, P, S, F, Cl, I, Br.
Citation Information
Patent Citations
Nano-porous metal powder and preparation method thereof
CN111334682A